Penyusunan Rancangan Progam Pengembangan Behavioural Competencies untuk Menunjang Kualitas Kehidupan Kerja Pegawai di PT. X - Khiat, Vanessa; Halim S., L. Verina; Hariyanto, V. Heru (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2021)
This study aims to develop a program for developing behavioral competencies that are suitable to support the quality of work life of employees at PT. X, especially by increasing the dimensions of competency development. The definition and dimensions of work life quality that will be used in this study refer to the definition put forward by the European Foundation for Improvement of Living and Working Condition (EWON). The quality of work life has five dimensions, namely health and well-being, job security, job satisfaction, competency development, and work and non-work life balance. This study uses research and development design with an explanatory sequential mixed methods approach consisting of three stages. First, the pre-assessment stage is carried out to determine the condition of the quality of work life at PT. X in general, as well as the five-dimensional conditions. Secondly, the assessment phase was conducted to find out the competency development tools owned by PT. X, as well as obstacles, needs, or expectations that want to be overcome or fulfilled by PT. X is related to competency development. Third, at the intervention stage compiled competency development tools that are in accordance with the needs of PT. X, such as competency models, guidance on behavioral based interviews, competency excavation questionnaires and critical incident forms, competency assessment recap form, and examples of strategic orientation competency interventions.